Pengaruh Profitabilitas, Likuiditas, Pertumbuhan Penjualan, dan Operating Capacity terhadap Financial Distress: (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Apparel and Luxury Goods yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023) - Silvi Al Waaliy; Slamet Mudjijah (Jurnal bintang manajemen, 2025)
This study aims to determine the influence of Profitability, Liquidity, Sales Growth, and Operating Capacity on Financial Distribution on the clothing and luxury goods sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. The sampling technique used is Non Probability Sampling with a sample of 9 companies in the clothing and luxury goods sub-sector listed on the Indonesia Stock Exchange for the 2019-2023 period. In this study, a multiple linear regression method was carried out assisted by the SPSS version 29 program and Microsoft Excel 2010. The results showed that (1) Profitability had no effect on Financial Distress, (2) Liquidity had an effect on Financial Distress, (3) Sales Growth had no effect on Financial Distress, (4) Operating Capacity had an effect on Financial Distress.